Experimental investigation of an advanced organic Rankine vapor compression chiller - Grauberger, Alex Michael, author; Bandhauer, Todd, advisor; Quinn, Jason, committee member; Windom, Bret, committee member; Sharvelle, Sybil, committee member (Colorado State University. Libraries, 2022)
Thermally driven chilling technologies convert heat into cooling. These systems can support increasing cooling demands using waste heat in a variety of applications. Commercial thermally driven chilling technologies suffer from several implementation challenges, including high capital costs, limited equipment lifecycles, rigid working principles, and large physical formats, and thus are not implemented widely. Organic Rankine vapor compression cooling systems are a pre-commercial technology which can address the limitations of commercial alternatives. Organic Rankine vapor compression cooling systems couple an organic Rankine power generation cycle to a standard vapor compression chilling cycle. These systems can use benign, pressurized refrigerants as working fluids which allows for reduced heat exchanger costs over commercial thermally driven alternatives without environmentally impactful fugitive emissions. Refrigerants are released from cooling technologies during charging, leaking connections, and/or improper/unregulated disposal. Furthermore, the coupling of the two individual cycles allows the use of high-speed compression and expansion machinery as well as multiple methods of heat recuperation. High-speed fluid machinery and heat recuperation strategies reduce the format and cost of the technology while simultaneously improving the longevity and operational flexibility. Current organic Rankine vapor compression efforts are limited from an absence of experimental validation. This study aims to fill this research gap through investigating a prototype organic Rankine vapor compression system enhanced with a high-speed, centrifugal turbo-compressor, sub cycle and cross cycle heat recuperation, compact heat exchanger technologies, and benign, next-generation refrigerants at an industry-relevant scale of 300 kW. A thermodynamic model was created and a system heat-to-cooling coefficient of performance (COP) of 0.65 was simulated with 91°C liquid waste heat, 30°C condenser coolant, and 7°C chilled water delivery where a 5°C inlet to outlet temperature difference was specified for each stream. A full-scale prototype was fabricated and tested following standards for performance rating of commercial water chilling technologies to validate the performance simulation. Experimental testing of the prototype yielded a thermal COP of 0.56 and a cooling duty of 264 kW under its baseline operating conditions. The baseline test conditions were identical to the simulated conditions except the temperature difference across the condensers, which was 1.7°C greater due to a 25.6% lower condenser coolant flowrate. The lower condenser coolant flowrate, a vapor compression condenser refrigerant outlet vapor mass quality of 6.2% instead of the modeled 1°C of subcooling, and elevated system pressure losses limited the efficiency and cooling duty of the prototype over the simulated values. A scenario analysis on the test data was complete to show the prototype could surpass the simulated performance prediction with a COP of 0.66 at 300 kW of cooling if the operational limitations associated with prototype were corrected. This performance is competitive with commercial single-effect absorption systems and is possible because the turbomachinery efficiencies were high. The isentropic efficiency values for the turbine and compressor were 76.7% and 84.8% respectively at the baseline conditions during experimentation and the two devices had a 100% power transmission efficiency within experimental error. Following the assessment of baseline performance, operational characteristics of the technology were quantified at off-design boundary conditions and normalized to those of the baseline to identify performance trends. It was shown that prototype thermal performance generally improved with increasing waste heat supply temperature, increasing chilled water delivery temperature, decreasing condenser coolant temperature, and decreasing chilling duty. These trends are consistent with performance simulations in literature. However, performance improvements at off-design operation were often challenged by variations in turbine and compressor efficiency as well as the efficacy of heat recuperation strategies. Such changes to component performance characteristics at varying boundary conditions have not been previously quantified in practice and, thus, have historically been neglected in analytical investigations of organic Rankine vapor compression systems. Understanding the off-design component performance characteristics allows for the creation of validated organic Rankine vapor compression performance models. Such models will be critical to understanding the true energy savings potential of organic Rankine vapor compression systems as they are continuously investigated.
Keywords: experimentation; turbomachinery; waste heat recovery; organic Rankine cycle; district cooling; vapor compression cycle